Five Applications of Narrative Exposure Therapy for Children and Adolescents Presenting With Post-Traumatic Stress Disorders - Fazel, Mina; Stratford, Hannah J.; Rowsell, Eleanor; Chan, Carmen; Griffiths, Helen; Robjant, Katy (Frontiers in Psychiatry, 2020)
Narrative Exposure Therapy (NET) is an individual therapeutic approach that has an emerging evidence base for children. It was initially trialed with refugee and asylum seeking populations, in both high and low and middle income settings, utilising either lay or professional therapists. The results of treatment trials for PTSD in refugee children with NET (or the child ‘KIDNET’ adaptation) demonstrates how this is an effective intervention, is scalable and culturally dexterous. This paper describes, in five cases from clinical practice settings, the applicability of NET into broader, routine practice. The cases outlined describe the use of NET with children and adolescents with: Autism Spectrum disorders, psychotic symptoms and intellectual disabilities; histories of forced abduction into child soldiering; complex physical health problems needing multiple interventions; and victims of childhood sexual abuse. The cases are discussed with regards to how the NET lifeline facilitated engagement in treatment, practical adaptations for those with intellectual disabilities and how NET, with its relatively short training for health professionals, can be modified to different contexts and presentations. The importance of improving access to care is discussed to ensure that young people are supported with their most complex and disruptive memories.